Coastal roads atlas. Reshaping daily infrastructures for coastline adaptation - Chiara Nifosì; Federico De Angelis; Rawad Choubassi; Andrea Gorrini; Federico Messa (TeMA: Journal of Land Use, Mobility and Environment)
The widespread poor quality that characterizes many cities and urbanization today is often related to the outdoor spaces. These conditions are common situations in many contexts of our country but are intensified where spatial inequality and environmental vulnerability converge. Although declined in different territories these situations have at their center the complex space of the road. The road system not only contributes significantly to climate change but is also the main victim of the consequences related to these changes. The research investigates the role of the roads and parking spaces, interpreted as the main background of our everyday lives, in facilitating socio-ecological transition of most fragile territories. Particular attention is paid to the different vulnerabilities of Italian coastline and to the ways in which adaptation measures can be implemented to mitigate risks. The initial analyses are focused on developing methods to measure and evaluate the climatic, geophysical, and socio-economic vulnerabilities of coastal roads, which are rendered, through aggregated maps of quantitative and qualitative indicators, in an "Atlas of Coastal Roads". The Atlas is conceived as an operational tool, able to guide stakeholders to develop national and place-specific interpretations.